2021
DOI: 10.3389/fmicb.2021.619028
|View full text |Cite
|
Sign up to set email alerts
|

Developing Innolysins Against Campylobacter jejuni Using a Novel Prophage Receptor-Binding Protein

Abstract: Campylobacter contaminated poultry remains the major cause of foodborne gastroenteritis worldwide, calling for novel antibacterials. We previously developed the concept of Innolysin composed of an endolysin fused to a phage receptor binding protein (RBP) and provided the proof-of-concept that Innolysins exert bactericidal activity against Escherichia coli. Here, we have expanded the Innolysin concept to target Campylobacter jejuni. As no C. jejuni phage RBP had been identified so far, we first showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
(77 reference statements)
1
28
0
Order By: Relevance
“…For example, phage endolysins have a broader host specificity than lytic phages ( Siringan et al, 2011 ). Along these lines, Zampara et al (2021) suggested the application of phage-derived enzymes instead of lytic phages to overcome some of the problems inherent with intact phages. Endolysins are phage-programmed enzymes that destroy the peptidoglycan layer when externally added leading to osmotic imbalance and cell death ( Zampara et al, 2021 ).…”
Section: Future Strategies For Optimizing Phage Application In Poultry Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, phage endolysins have a broader host specificity than lytic phages ( Siringan et al, 2011 ). Along these lines, Zampara et al (2021) suggested the application of phage-derived enzymes instead of lytic phages to overcome some of the problems inherent with intact phages. Endolysins are phage-programmed enzymes that destroy the peptidoglycan layer when externally added leading to osmotic imbalance and cell death ( Zampara et al, 2021 ).…”
Section: Future Strategies For Optimizing Phage Application In Poultry Productionmentioning
confidence: 99%
“…Along these lines, Zampara et al (2021) suggested the application of phage-derived enzymes instead of lytic phages to overcome some of the problems inherent with intact phages. Endolysins are phage-programmed enzymes that destroy the peptidoglycan layer when externally added leading to osmotic imbalance and cell death ( Zampara et al, 2021 ). Although endolysins have successfully been used in an antibacterial application and can exhibit low development of resistance, their application is currently more suitable toward Gram-positive bacteria, as Gram-negative bacteria contain an outer membrane that inhibits entry of endolysins to the peptidoglycan layer ( Gutiérrez and Briers, 2021 ).…”
Section: Future Strategies For Optimizing Phage Application In Poultry Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…12–14 The study of phages and their genomes is therefore inherently valuable to advance our understanding in a diversity of fields including molecular biology, ecology, evolution, bacterial pathogenesis, biotechnology, and health. Understanding phage genomes will certainly create opportunities to translate novel phage proteins and phages themselves into potent biotechnological 15 and medical tools. 16 Here we isolated and sequenced the genomes of four novel phages infecting Klebsiella pneumoniae, an increasingly relevant pathogen identified by the World Health Organization as priority for the development of new antibiotics.…”
Section: Introductionmentioning
confidence: 99%